Topographic influences on wind near Green River, Utah: technical report - Hsi, George, author; Binder, G. J., author; Cermak, J. E., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1968)
Actual terrain near Green River, Utah, was modeled to a scale of 1:800. The purpose of this study was to find the effect of topography on wind speed and wind direction. Field data are included in this report and comparisons between model and prototype data are made. Throughout this study, an ambient wind velocity of 4.57 mps was used and a neutral flow condition was maintained in the Army Meteorological Wind Tunnel.
CER67-68GH-GJB-JEC54.
April 1968.
Prepared under U.S. Army Research Grant DA-AMC-28-043-65-G20 U.S. Army Material Command Washington 25, D.C. for Atmospheric Science Office Atmospheric Science Laboratory White Sands Missile Range.
Keywords: Winds -- Green River (Wyo.-Utah)